Isolation and Identification of Microorganisms During the Spontaneous Fermentation Process of Cassava into Kabuto, a Traditional Food from Muna, Southeast Sulawesi - Ilian Elvira; Baihaqi; Mariani L; Andi Dahlan; Nur Suci; Agry Anugrah Pertiwi (Journal of Food and Agricultural Product, 2026)
Kabuto is a traditional fermented food originating from Muna Regency, Southeast Sulawesi, Indonesia, made from cassava through a spontaneous fermentation process. The presence of microorganisms during fermentation plays an important role in the development of sensory characteristics such as flavor, aroma, texture, and ultimately determines the final quality of the product. This study aimed to isolate and identify microorganisms involved in the fermentation process of kabuto. Microbial isolation was conducted on days 0, 2, 4, and 6 of fermentation using the pour plate and spread plate methods on de Man, Rogosa and Sharpe Agar (MRSA), followed by incubation at 37 °C for 48 hours. The resulting colonies were enumerated using the Total Plate Count (TPC) method, and Gram staining was performed to determine the characteristics of bacteria present during fermentation. The results showed that the microbial population increased gradually throughout the fermentation process, reaching the highest count on day 6 at 1.68 × 10^8 CFU/g. Gram staining results indicated that the microbial population was dominated by Gram-positive bacteria, suggesting the presence of lactic acid bacteria as the primary microorganisms involved in fermentation. Gram-negative bacteria were detected at the early stage, likely originating from raw materials and the surrounding environment. The dominance of lactic acid bacteria has positive implications for product safety due to pH reduction and inhibition of pathogenic microorganisms. However, the presence of Gram-negative bacteria in the early stage indicates a potential risk of contamination if proper sanitation is not maintained. Therefore, process control and hygienic practices are essential to ensure the safety of kabuto. Further studies are recommended to perform molecular identification and evaluate food safety parameters. Keywords: lactic acid bacteria, fermentation, Kabuto